The adverse health effects associated with drought in Africa: working towards developing a vulnerability index - Asmall, Taherah (Department of Public Health and Family Medicine, 2020)
Africa is uniquely vulnerable to the occurrence of drought. A rise in temperatures over Southern Africa occurs at almost twice that of the global rate. South Africa has begun to experience an increase in the frequency of drought, particularly in the Western and Eastern Cape. Droughts are associated with several health effects. The direct and indirect risks of climate change to human health have become a global concern. The most recent systematic review available on the adverse health effects associated with drought was published in 2013, and as such, an up-to-date review focusing on Africa is needed to inform a Cape Town specific health vulnerability index. This study aims to provide a review of available research exploring the association between drought and adverse health effects in Africa. The rationale for this study is to provide a solid research foundation from which a drought-specific health vulnerability index for Cape Town can be developed. A narrative review of original studies and published reviews was conducted. An extensive electronic literature search was performed using a combination of keywords, Medical Subject Heading (MeSH) terms and free text words. The Critical Appraisal Toolkit (CAT) was used to assess the quality of included studies. A total of 1922 publications were identified, of which twenty-four articles were included in this review. The main drought-related health effects that emerged were divided into 4 main categories: (1) drought and nutritional health including malnutrition, poor childhood health outcomes (wasting, stunting and underweight), mortality, anaemia, and nutritionrelated disability; (2) drought and food consumption including micronutrient deficiencies and motor neuron diseases; (3) drought and water-borne, water-washed and water- related diseases including cholera outbreaks, diarrhoeal diseases, protozoa parasite transmission, scabies outbreaks, trachoma, vector-borne disease outbreaks and malaria-related mortality; and (4) drought and health behaviours including health perceptions and health-seeking behaviours, HIV prevention and care behaviours and family planning practices. There was generally limited evidence in all health categories with several limitations. These limitations include studies with methodological weaknesses (e.g. a lack of comparison to a non-drought period), the singularity of published studies on health effects associated with drought and studies which did not account for potential confounders. While the evidence from the included studies is limited, this study highlights gaps in literature to encourage further research into understanding the direct and indirect impacts of drought on health, particularly in vulnerable groups. Furthermore, the results of this study emphasized the contextual factors which lower an individual's adaptive capacity and identified key indicators that can be used to begin to develop a broad framework for a vulnerability index